Infrastructures critiques, vulnérabilisation du territoire et résilience : assainissement et inondations majeures en Île-de-France - Annabelle Moatty; Magali Reghezza-Zitt (VertigO)
Although sanitation networks are critical infrastructures, their impact on territorial vulnerability and social resilience is still underestimated. The role played by the energy, transport and telecommunication networks in crises and post-disaster recovery is better understood, both from a theoretical and operational point of view. On the contrary, sanitation networks remain poorly appreciated and their vulnerability is underestimated. Based on the study of the Parisian metropolitan area, this paper aims to show that sanitation networks are critical components in crisis management, post-disaster recovery and reconstruction. First, we address the links between security and critical infrastructures. Then, we present the case of sanitation in Île-de-France. Finally, we discuss how sanitation system is taken into account in preparedness to major floods and describe the potential consequences of its damage or failure for crisis management and post-disaster recovery.